The archaeological implications of water-cached hyena kills - Selvaggio, M.M. (Current Anthropology, 1998)
11 citations (Crossref) [2023-10-31]
Keywords: dept.ant

Concerning the three stage model of carcass processing at FLKZinjanthropus: A reply to Capaldo - Selvaggio, Marie M (Journal of Human Evolution, 1998)
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/004-801-145-000-921 tex.type: [object Object]
Keywords: Animals; Anthropology; Carnivora; Feeding Behavior; Fossils; Hominidae; Humans; Models; Biological; animal; anthropology; biological model; dept.ant; feeding behavior; fossil; hominid; human; note; peer-reviewed; ⛔ No DOI found

Evidence for a three-stage sequence of hominid and carnivore involvement with long bones at FLKZinjanthropus, olduvai gorge, tanzania - Selvaggio, Marie M (Journal of Archaeological Science, 1998)
The order in which hominids and carnivores had access to Plio-Pleistocene bone assemblages has defied interpretation despite attempts to decipher their sequence from element frequencies or by comparing ancient butchery marks with modern ones. Data from two simulations in which experimental stone-tool butchery of long bones occurred after carcasses were defleshed by large free-ranging East African carnivores are here compared to data from the FLK Zinjanthropus bone assemblage from Olduvai Gorge, Tanzania. One experimental sample simulated two stages of tissue removal; defleshing of long bones by carnivores, followed by tool-assisted flesh-scrap removal and marrow extraction. A second simulated three stages of tissue removal; the first two stages the same as the first sample, plus a third stage in which bone-crunching carnivores ravaged the remains. Carnivore ravaging is demonstrated to result in additional tooth marks on epiphyseal fragments, but does not significantly alter the incidence of defleshing tooth marks or butchery marks on midshafts. The Zinjanthropus sample is similar to the three-stage simulation in its proportion of epiphyseal relative to midshaft fragments, and for the incidence of midshafts bearing tooth marks and butchery marks. © 1998 Academic Press Limited.
86 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-024-831-197-63X tex.type: [object Object]
Keywords: Butchery Marks; Carnivore Tooth Marks; Experimental Archaeology; Pleistocene; Pliocene; Scavenging; Site Formation; Tanzania; Taphonomy; archaeology; bone assemblage; dept.ant; taphonomy

Lust for life and fear of the alien: Ethnology in the Third Reich - German - Hauschild,T - Messing, Simon D (American Anthropologist, 1997)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-002-691-486-562 tex.type: [object Object]
Keywords: dept.ant

Hierarchy and caste - history and political-structure of the Dizi in southwestern Ethiopia - German - haberland,eh - Messing, Simon D (American Anthropologist, 1995)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-971-770-956-778 tex.type: [object Object]
Keywords: dept.ant

Cultures in images - German - Raabe,EC, Wagner,H - Messing, Simon D (American Anthropologist, 1995)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/071-168-026-695-58X tex.type: [object Object]
Keywords: dept.ant

Age and status - ethnological contributions on modern sociological-research on age - German - Marzi,H - Messing, Simon D (American Anthropologist, 1992)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-886-136-189-537 tex.type: [object Object]
Keywords: dept.ant

Der Tod—Ende oder tor zum leben? Tod und jenseitsvorstellungen der völker. josef franz thiel - Messing, Simon D. (American Anthropologist, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1991GW38400034 tex.unique-id: [object Object]
Keywords: dept.ant

Mythology - tours through tradition and the present - German- Schlatter,G - Messing, Simon D (American Anthropologist, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/152-955-033-839-536 tex.type: [object Object]
Keywords: dept.ant

Book Review: Beyene tadesse. proceedings of the 8th international conference of ethiopian studies, university of addis ababa, 1984 . vol. 1, 846 pp., vol.2, 737 pp. place of publication not reported: institute of ethiopian studies, 1988. figures, maps, illustrations, tables. - Messing, Simon D (African Studies Review, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-482-403-237-222 tex.type: [object Object]
Keywords: book.review; dept.ant

Africa and Israel - Relations in Perspective - Ojo,o - Messing, SD (Africa Today, 1990)
tex.unique-id: ISI:A1990EV47100007
Keywords: dept.ant; ⛔ No DOI found

The circumcision of women - a strategy for eradication - kosothomas,o - Messing, SD (Africa Today, 1990)
tex.unique-id: ISI:A1990DD01200016
Keywords: dept.ant; ⛔ No DOI found

Social/Cultural anthropology: chosen voices: the story of the american cantorate. mark slobin - Messing, Simon D (American Anthropologist, 1990)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-341-842-377-404 tex.type: [object Object]
Keywords: dept.ant

Changing patterns of land use by Plio-Pleistocene hominids in the Lake Turkana Basin - Rogers, M.J.; Harris, J.W.K.; Feibel, C.S. (Journal of Human Evolution, 1994)
117 citations (Crossref) [2023-10-31]
Keywords: dept.ant; peer-reviewed